Effect of appropriate extenders to maintain sperm functionality during short-term storage of sterlet (Acipenser ruthenus) sperm with fertilization assay under hatchery conditions - Shazada, Nururshopa Eskander; Siddique, Mohammad Abdul Momin; Zhang, Songpei; Ma, Zhijun; Rodina, Marek; Linhart, Otomar (Fish physiology and biochemistry, 2025)
Short-term storage and management of sperm in vitro is an easy and economical process in which suitable extenders can be utilized to extend the storage period and prevent sperm function impairment. Therefore, the current study aimed to evaluate the effect of suitable extenders during the short-term storage of sterlet sperm and determine their fertilizing capacity and hatching success. Three extenders containing a composition of 16, 20, and 24 mM NaCl, 1 mM KCl, 0.1 mM CaCl2, 10 mM Tris, pH 8.0 with osmolarity of 46, 55, and 62 mOsm/kg, were used to dilute the sperm of four sexually mature sterlet males (n = 4). Using a CASA system, the motility and velocity of undiluted and diluted sperm with extenders (E1 - E3) were assessed over 6 days at 0-2 °C. The short-term stored diluted sperm was then used in the fertilization and hatching assay, and undiluted fresh and stored sperm was used as a control. A two-way factorial analysis of variance (ANOVA) model confirmed significant effects on sperm motility, curvilinear velocity (VCL), and straight-line velocity (VSL) (P < 0.001), as well as their interaction with the extender. The model was decomposed into a one-way ANOVA to examine the impacts of extenders and storage time. With increasing storage periods, the sperm motility and velocity gradually decreased for diluted sperm with three extenders (E1-E3) but sharply decreased for undiluted sperm (Control). The motility of undiluted sperm was found 3.77 ± 4.09% at 4 days, whereas sperm diluted with extenders showed 57.57 ± 12.33% (E1), 64.34 ± 11.86% (E2), and 61.40 ± 12.41% (E3) motility at 6 days. This study explored extenders optimized with higher osmolarity (39-62 mOsm/kg) and lower K+ (1 mmol/L) as the most suitable medium for storing sterlet sperm for 6 days. After 6 days post storage, sperm diluted with extenders E1-E3 achieved a fertilization rate of 31.29 ± 14.2%, 31.66 ± 8.84%, and 30.67 ± 10.02%, respectively, and hatching success of 29.58 ± 13.4%, 30.50 ± 7.89%, and 27.95 ± 9.62%, respectively with freshly ovulated eggs.
Keywords: uchování spermatu; fertilizace; Semen Preservation; Sperm Motility; mužské pohlaví; Sperm velocity; Sperm short-term storage; Sperm motility; Fertilization; CASA; zvířata; Hatching rate; motilita spermií; Fishes; Fertilization rate; ryby; Spermatozoa; spermie; Male; Animals